DAMPAK TAX ACCOUNTING CHOICES TERHADAP TAX AGGRESSIVE - Harnovinsah, Harnovinsah; Mubarakah, Septyana (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2016)
Penelitian ini bertujuan untuk menganalisis tax accounting choices, defferen tax expense dan firm size sebagai indikator tax aggressiveness. Sampel yang digunakan penelitian ini sebanyak 50 perusahaan manufaktur yang terdaftar di Bursa Efek Indionesia (BEI) selama periode 2010-2014. Sampel diambil dengan cara purposive random sampling dengan menggunakan criteria tertentu. Tax accounting choices diukur dengan pemilihan metode garis lurus dan metode FIFO dengan variabel dummy, sedangkan untuk deffered tax expense diukur dengan membandingkan deffred tax expense dengan total asset.Firm size diukur dengan melakukan logaritma natural total asset. Hasil penelitian ini menemukan bahwa metode garis lurus berpengaruh signifikan negative terhadap tax aggressiveness sedangkan metode FIFO tidak berpengaruh terhadap tax aggressiveness. Deffered tax expense berpengaruh signifikan negative terhadap tax aggressiveness dan firm size berpengaruh signifikan negative terhadap tax aggressiveness. Sehingga dapat dikatakan bahwa metode garis lurus dan deffered tax expense dapat dijadikan sebagai indikator tax aggressivenessTax Accounting choices in this study chose the straight-line method and the FIFO method,which is the management actions in determining the policies that are applied to compile financial statements and used as an indicator of tax aggresivitas. In addition the study also used the deffered tax expense and firm size as another independent variable to measure the tax aggresivitas action of the tax aggressiveness. This study aims to analyze the tax accounting choices, defferen tax expense and tax firm size as an indicator of tax aggressiveness. The samples used in this study as many as 50 manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2010-2014. The sample were with how purposive random sampling by using certain criteria. Tax accounting choices is measured by the selection of the method of straight line method and the FIFO method with dummy variables, whereas for deffered tax expense is measured by comparing the deffred tax expense by total assets. Firm size is measured by taking the natural logarithm of total assets. The results of this study found that the straightline method significant negative effect against the tax aggressiveness. while the FIFO method has no affect against tax aggressiveness. Deffered tax expense significant negative effect on tax aggressiveness and firm size are significant negative effect against tax aggressiveness. So it can be said that the method of straight-line and deffered tax expense can be used as an indicators of tax aggressiveness.